Office 365 video - Hill, Robbie; Safari eBooks ([Place of publication not identified] : [Intellezy], 2017)
"Video is an app included in Microsoft Office 365 which allows a user to upload, share, stream, and play videos. In this course, students will gain a comprehensive overview of Video, including how to navigate in the app and how to watch videos. They will also learn how to search for videos, as well as use channels as a way to organize and share videos. In addition, students will learn how to edit channel settings, share videos with others, and edit permissions in Office 365 Video. "--Resource description page.
Presenter, Robbie Hill.
Title from title screen (viewed May 19, 2017).
Imprint from resource description page.
Keywords: Microsoft Office; Small business -- Computer programs; Digital video; Electronic books